A retrospective analysis of the utility and safety of kidney transplant biopsies by nephrology trainees and consultants. (April 2018) - Reschen, Michael E.; Mazzella, Andrea; Sharples, Edward
Abstract: Background and aims: Dysfunction of a kidney transplant often requires histological sampling by percutaneous ultrasound-guided core needle biopsy. Transplant biopsy is more specialized than native kidney biopsy, the indications and complications are less well defined and in England are performed mainly by nephrologists. The aims of the study were to evaluate the adequacy and complication rate in living and deceased donor recipients according to training status of the nephrologist, assess the accuracy of physicians in predicting rejection, the threshold creatinine rise for biopsy, and the change in drug management post-biopsy. Materials and methods: We performed a retrospective analysis of all adult patients undergoing a kidney transplant biopsy in 2015 at a major teaching hospital in the UK as part of a service evaluation program. The primary outcome measure was the rate of major complications and secondary measures included sample adequacy, seniority of operator, clinician-predicted diagnosis, biopsy diagnosis and change in drug management. Results: One hundred and seven (n = 107) transplant biopsies were performed across 27 living donor (LD) recipients and 57 deceased donor (DD) recipients. LDs were statistically less likely to have diabetes, more likely to take azathioprine. Biopsies were performed by trainees rather than consultants at a ratio of 3:1. The complication rate was low with no major bleeding complications. Visible haematuria occurred in 4.7% and 2.8% of patients developed transplant pyelonephritis. 3.7% of biopsies contained no glomeruli. There was no effect attributed to training status. The pre-biopsy rise in creatinine was significantly less for LD compared to DD recipients (45% vs 70%). A clinician-suspected diagnosis of rejection was confirmed on biopsy in 42.9% of cases and overall about 47.9% of biopsies led to a change in drug management. Conclusions: Kidney transplant biopsies were safe, performed adequately by trainee nephrologists and were often associated with a change in drug management. Highlights: Transplant biopsy is commonly performed with a risk of major bleeding complications. In 107 consecutive kidney transplant biopsies in one calendar year there were no major complications. Trainees performed more biopsies than consultants with no adverse effect on safety or biopsy quality. Rejection was correctly predicted in 43% of cases and 48% of biopsies were associated with a change in drug management. A significantly smaller rise in creatinine occurred before biopsy in living compared to deceased donors.